(untitled) (Semiárida, 2022)
The application of different combinations of cutting frequencies and intensity, as well as variation in the combination of cutting frequency and intensity, during the growing season can determine changes in various plant attributes. Knowledge of the response to different defoliation regimes of the species Panicum coloratum L. is limited. The objective of this study was to determine the effect of defoliation pattern (frequency and intensity of defoliation and the variation in the combination of these management variables during the growing season) on perennial millet plants (P. coloratum L. var. coloratum) cv Green. The test was carried out in a greenhouse under controlled conditions. The treatments consisted of the combination of two frequencies (2.5 and 5.0 expanded leaves.macollo-1 for frequent (F) and infrequent (I), respectively) and two intensities (50 and 100 mm for severe (S) and lax (L), respectively) cutting (FS, FL, IS, IL). In addition, two treatments were established with two severe (FS IL) and lax (FL IL) frequent defoliations followed by another period with lax defoliation and two treatments with one severe (IS FS) and lax (IL FS) infrequent defoliation followed by a period with two frequent severe defoliations. Frequent and severe defoliation regimes achieved lower above-ground and underground biomass at the end of the experience, and in turn increased tiller mortality with respect to IL. On the other hand, the combination of these two defoliation regimes allowed increasing the accumulation of aerial and underground biomass and, in turn, maintaining at the end of the growing season the population of tillers generated with frequent severe cuts at the beginning of the season. same (C1 and C2). Knowledge of the effects of defoliation on the plant is essential to carry out management that guarantees the production and persistence of a pasture in semi-arid environments. Director: Ferri, Carlos María